Bacteria Patterns and Antibiotic Sensitivities in Patients with Preterm Premature Rupture of Membrane: Study of Patients with PPROM ≤ 6 Hours And > 6 Hours at General Hospital Kariadi Semarang - Rio Bornfry Haro Munthe; Besari Adi Pramono; Endy Cahyono Kristiawan; Agoes Oerip Poerwoko; Ratnasari Dwi Cahyanti (Diponegoro International Medical Journal, 2025)
Background: Preterm premature rupture of membranes (PPROM) has multifactorial causes. Ascending bacterial invasion can cause intrauterine infection in up to 60% of cases with PPROM. Giving antibiotics at inadequate concentrations causes bacteria to grow exponentially, which is characterized by very fast growth.Objective: This study aims to determine bacteria patterns and antibiotic sensitivity in patients with PPROM at Dr. RSUP. Kariadi, Semarang.Methods: Observational analytical research with a cross-sectional design. The research subjects were 46 pregnant women aged 20-36 weeks 6 days who experienced PPROM. The selection of research subjects was carried out using the consecutive sampling method, namely the selection of research subjects based on research criteria and the subjects signed an agreement to participate in the research. The independent variables in this study were preterm PPROM ≤ 6 hours and > 6 hours, the dependent variables in this study were bacteria patterns and antibiotic sensitivity. The data that has been obtained is analyzed using the SPSS program. Results are significant if p<0.05.Results: Escherichia coli and Candida albicans are the most found pathogens. The antibiotics vancomycin, meropenem, and amphotericin B are effective in patients with PPROM. Women who experienced PPROM ≤ 6 hours and > 6 hours did not have significant differences in bacteria patterns and antibiotic sensitivity results.Conclusion: The gram-negative rod-shaped bacteria Escherichia coli and the fungus Candida albicans are the main pathogens that cause PPROM. The administration of vancomycin, meropenem, and amphotericin B has high effectiveness in PPROM patients at RSUP dr. Kariadi Semarang.